55.2k views
4 votes
Help me with this plssss
divide this​

Help me with this plssss divide this​-example-1
User Cwharland
by
4.6k points

1 Answer

6 votes

Answer:

1 - y + y²

Explanation:

1 + y³ is a sum of cubes and factors in general as

a³ + b³ = (a + b)(a² - ab + b²) , then

1 + y³

= (1 + y)(1² - 1(y) + y²) = (1 + y)(1 - y + y²)

Then


(1+y^3)/(1+y)

=
((1+y)(1-y+y^2))/(1+y) ← cancel out the common factor (1 + y)

= 1 - y + y²

User Steven Graham
by
6.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.